Jaminan Atas Pemenuhan Hak Keamanan Data Pribadi Dalam Penyelenggaraan E-Government Guna Mewujudkan Good Governance - Bunga Asoka Iswandari (Fakultas Hukum Universitas Islam Indonesia, 2021)
This paper focuses on discussing the integration between the implementation of e-government as an alternative to public services with the principles of good governance and the existence of legal guarantees in the implementation of e-government that can fulfill the right to personal data for private information contained in the e-government system. The study was conducted using the library research data collection method and analyzed prioritizing logical thinking so as to find the cause and effect that will occur and this writing is a qualitative normative legal research. Bureaucratic reform to digital direction will be an improvement step for public services because through the digital bureaucracy the dream of realizing good governance in Indonesia becomes even more real. The electronization of communication between the public service sector and society, which is implemented with the existence of e-government, is an effort to create a digital bureaucracy. In practice, the e-government system contains a lot of information, both public and private. Data security, which is private information from every community, is very important in relation to e-government, public trust will be greatly affected by data security issues. However, the laws and regulations in Indonesia do not yet regulate the protection of personal data. Whereas the security of a citizen's personal data is a right that must be fulfilled by the state, therefore the government must have a legal guarantee mechanism that can create a safe e-government system.